(untitled) (Journal of the College of Basic Education, 2025)
The research aims to prepare two scales (for psychological shyness and sports orientation) in order to identify the correlation between psychological shyness and sports orientation towards track and field games for intermediate school students. To achieve this aims, the researcher used the descriptive approach and the survey method. The research sample was represented by second-year intermediate school students from (6) intermediate schools in Kufa district, Najaf governorate. The number of students in these schools reached (671) students. Using the random method and the equal method, different samples were drawn from the statistical community of the current research according to its purpose. There were (30) students for the exploratory experiment sample, (240) students for the purpose of standardizing the scales, and (180) students for the purpose of the application sample. Then the researcher reviewed previous studies and used the psychological shyness scale prepared by (Hawra Abbas Karmash: 2009) since the scale achieves the intended research goal, which is to know the level of sports orientation. The scale consists of (27) paragraphs, with three alternatives: (applies to me completely, applies to me sometimes, does not apply to me at all). The scale score ranges from (81-27). She also used the sports orientation scale prepared by (Abu Ghazal: 2012) since the scale achieves the intended research goal, which is to know the level of sports orientation. The scale consists of (25) paragraphs, with five alternatives: (applies to me completely, applies to me a lot, applies to me sometimes, applies to me a little, does not apply to me at all). The scale score ranges from (125-25). Then the researcher worked on making some modifications to the scale in terms of the type of activity to suit the activity of the arena and field. Then the researcher confirmed the validity of the scales from a statistical point of view. After they were ready, she began applying the scales to the research sample. After obtaining the results, the researcher used the statistical program (SPSS27.1) for the purpose of analyzing the data. Accordingly, the researcher concluded that the prepared scales were able to measure what they were designed for, as well as the existence of a correlation between psychological shyness and the athletic orientation of female students.